2012
DOI: 10.3846/13926292.2012.662659
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Experiments With Single Mode Gyrotron Equations

Abstract: Gyrotrons are microwave sources whose operation is based on the stimulated cyclotron radiation of electrons oscillating in a static magnetic field. This process is described by the system of two complex differential equations: nonlinear first order ordinary differential equation with parameter (averaged equation of electron motion) and second order partial differential equation for high frequency field (RF field) in resonator (Schrödinger type equation for the wave amplitude). The stationary problem of the sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In this paper we have implemented the equation system presented in [1]. This model is often described in the literature as an "old" equation system [13], because it does not take into account two physical effects:…”
Section: Time Dependent Approach Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we have implemented the equation system presented in [1]. This model is often described in the literature as an "old" equation system [13], because it does not take into account two physical effects:…”
Section: Time Dependent Approach Formalismmentioning
confidence: 99%
“…To solve the Schrodinger type linear partial differential field equation, the second order differential equation solver has to be used. In paper [13], the method of lines [8] with the "ode15s" solver was proposed. However, Matlab offers the "pdepe" function, which implements the second order algorithm that we have employed to find the solution.…”
Section: Solving the Electric Field Profile Equationmentioning
confidence: 99%
“…In [14] it was suggested that, for gyrotron time-dependent simulations, the BTCS may be preferable to the C-N on the grounds that C-N could be numerically unstable over long simulated time intervals. A discussion on this topic is beyond the scope of this paper.…”
Section: Ec-17 Workhopmentioning
confidence: 99%